RUNTUHNYA EKSKLUSIVITAS PEMBERITAAN: KAJIAN TERHADAP MOMEN KRITIS JURNALISME PADA MASA PANDEMI COVID-19 - Krisdinanto, Nanang; Apul, Merlina Maria Barbara (Interaksi: Jurnal Ilmu Komunikasi, 2024)
The Covid-19 pandemic created a critical moment in journalism that changed the journalistic production process and forced journalists to adapt their professional journalistic practices. On the other hand, the pandemic emerged when journalism transformed towards digital platforms that changed journalistic practices to be influenced by social media. This research looks at how journalists struggle to adapt their professional journalistic practices to digital challenges and the Covid-19 pandemic. This research uses a qualitative approach, case study method, and data collection techniques in the form of in-depth interviews and observations of online media journalists in Surabaya. The research findings show that the pandemic creates a critical moment of journalism in the form of destruction or accelerated destruction of the value of news exclusivity that has long prevailed in journalistic practice. This happened due to internal pressure from the editorial team, limited coverage mobility during the pandemic, and the development of digital applications making journalists carry out the practice of sharing news or information through digital groups.